EDUKASI DAN DETEKSI DINI DIABETES MELLITUS SEBAGAI UPAYA MENGURANGI PREVALENSI DAN RESIKO PENYAKIT DEGENERATIF DI DESA OELOMIN KABUPATEN KUPANG - Fitri Handayani; Domianus Namuwali; Riny Pujiyanti; Yustinus Rindu; Artha Abeatrix Ndun; Ongki Riwu; Kristoval Nuha Lara (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Diabetes mellitus (DM) is a non-communicable disease with increasing prevalence and is the main cause of various degenerative complications such as heart disease, kidney failure, and neuropathy. Education and early detection efforts play an important role in increasing public awareness of DM risk factors and the importance of early prevention and control. This promotive and preventive strategy is expected to reduce the prevalence of DM and the risk of long-term complications, and improve the overall health status of the community. Objective: to increase community knowledge and early detection of diabetes mellitus as an effort to reduce the prevalence and risk of degenerative diseases. The method of implementing this activity is by conducting education about Diabetes Mellitus and early detection of Diabetes Mellitus through blood sugar and blood pressure checks. The results of blood pressure examination obtained 83% normal blood pressure, 12% mild hypertension, 3% moderate hypertension 2% with severe hypertension. The results of blood sugar checks were 96% normal, 2% prediabetes and 2% diabetes